Identify success factors in industrial cooperatives using the critical Incident technique. - Hoseyn Vafaeibasir; Alireza Eslambolchi; Mansour Esmaeilpour; Ali Asgharisarem (تعاون و کشاورزی, 2021)
Investing in industry cooperatives, especially small and medium industries, has always been very important. Because in addition to playing a key role in a country's employment, it will also lead to economic growth and increase GDP. The purpose of this study is to investigate the factors that can lead to successful investment in small and medium industrial cooperatives and show a way for industrial entrepreneurs to enter this important economic field with more awareness. This research is a qualitative research based on the collected data of interviews with 15 industrial experts using the method of sensitive event technique and content analysis using MAX QDA 18 software. The last step of the final research model categories was obtained. The results showed that 5 general groups of factors including: managerial factors, entrepreneur related factors, production related factors, market factors and environmental factors can play an important role in the success of this type of investment. And private sector investors, including managers of production cooperatives, will help reduce investment risk by paving the way for better measures and paving the way for industrial growth and employment growth in the country.